Interactive Learning Content Using H5P in Pronunciation Course - Siregar, Alfina Gustiany; Sembiring, Friscilla (Mahesa Research Center, 2022)
In this blended learning, students experience offline and online learning. Sometimes students experience burnout in online learning. This can be caused by various things, such as signal interference, less interesting learning materials, and so on. In Pronunciation course, there are many symbols and transcripts on the pronunciation. More practice made the pronunciation of a word better. The purpose of this study is to developed interactive learning content using H5P in Pronunciation course. The method used is ADDIE model development method, the steps are analysis, design, development, implementation, and evaluation. The results are interactive video and interactive quizzes using H5P which are applied to students in Pronunciation course. Using interactive videos and interactive quizzes, students better understand the material and feel excited in the learning process.